IMPLEMENTASI STRATEGI MENGAJAR OUT DOOR TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH PONDOK PESANTREN FAJRUL IMAN KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Rahayu, Ahmad (Fakultas Agama Islam, 2020)
This study aims to determine the results of learning Arabic before and after the implementation of out-door teaching strategies, as well as the effect of implementing out-door teaching strategies on students' Arabic learning outcomes at Fajrul Iman Islamic Boarding School, Patumbak District, Deli Serdang Regency. The population in this study were all students of class VII. The research sample was determined as many as 28 students. Determined the sample using a randomized class technique. This research method is an experimental method. The data collection tool used was a test of learning outcomes in Arabic in the form of multiple choice objective, as many as 20 questions were tested before and after learning using the out door strategy. The conclusions obtained from this study are: the average value of the Arabic learning outcomes (pretest) of students before being taught using the out door teaching strategy is 63.39 category C (enough), the average value of the Arabic learning outcomes (posttest) of students after taught using out door teaching strategies is 80.17 category B (good). The results of students' Arabic learning after using the out door teaching strategy increased by 47.31% in the category of moderate improvement. The effect of implementing out door learning strategies on the learning outcomes of students in class VII MTs Fajrul Iman Islamic Boarding School, Patumbak District, Deli Serdang Regency in the 2019/2020 learning year was 55.84% So that out door teaching strategies are effectively used in improving Arabic learning outcomes.